Aligning Business Law with Rapid Technological Innovation: Challenges and Regulatory Strategies in the Digital Economy: Menyesuaikan Hukum Bisnis dengan Inovasi Teknologi yang Pesat: Tantangan dan Strategi Regulasi dalam Ekonomi Digital - Ida Ayu Anggun Tri Apsari; I Gede Agus Kurniawan (Indonesian Journal of Innovation Studies, 2026)
General Background: Rapid technological innovation has reshaped the digital economy and challenged the foundations of business law. Specific Background: Disruptive technologies, including artificial intelligence, blockchain, smart contracts, algorithmic platforms, and fintech ecosystems, increasingly operate beyond conventional legal assumptions rooted in static civil law frameworks. Knowledge Gap: Existing studies discuss dynamic competition, contract law disruption, and administrative regulatory theory separately, but they do not fully integrate these challenges into a holistic regulatory strategy for business law in the digital economy. Aims: This study aimed to examine theoretical and practical challenges in aligning business law with technological innovation and to formulate contemporary regulatory strategies through normative empirical legal research and comparative literature analysis of global standards, including the European Union, United Kingdom, and United States. Results: The findings identify three major legal challenges: dynamic competition in platform markets, disruption of contract law by autonomous agents and smart contracts, and fundamental rights risks related to algorithmic decision making, data governance, and cyber economic crime. The study also identifies Agile Governance, Regulatory Sandbox mechanisms, and Regulated Convergence as strategic responses to legal rigidity. Novelty: This study synthesizes adaptive law, agile regulation, sandbox governance, and regulated convergence into an integrated framework for digital economy business law. Implications: Regulators should move from prescriptive ex ante rule making toward continuous, risk based, iterative governance that balances innovation, consumer protection, market integrity, and legal certainty. Highlights: Static legal frameworks are unsuitable for fast moving digital ecosystems. Smart contracts and autonomous agents disrupt traditional contractual intent. Sandbox governance supports controlled innovation and risk mitigation. Keywords: Adaptive Law, Agile Regulation, Business Law, Digital Economy, Regulatory Sandbox